Physicochemical and biological evaluation of poly(ethylene glycol) methacrylate grafted onto poly(dimethyl siloxane) surfaces for prosthetic devices - Gonçalves, S. (2013)
Poly(dimethyl siloxane) (PDMS) was surface-polymerized with poly(ethylene glycol)methacrylate (PEGMA) by surface-initiated atom transfer radical polymerization (SI-ATRP) in aqueous media at room temperature. Modification of the PDMS surface followed a three-step procedure: (i) PDMS surface hydroxylation by UV/ozone exposure, immediately followed by (ii) covalent attachment of the initiator, 1-trichlorosilyl-2-(chloromethylphenyl)ethane, onto the hydroxylated PDMS, via chemical vapor deposition; finally (iii) PDMS surface-polymerization of PEGMA by ATRP. Modified PDMS was characterized by water contact angle measurement, SEM, FTIR-ATR, and XPS. Results showed that modified surfaces had a hydrophilic character, given the water contact angles around 60◦; FTIR-ATR and XPS analysis confirmed the presence of polymerized PEGMA on the surface of PDMS and the adhesion of Staphylococcus aureus GB 2/1 and Streptococcus salivarius GB 24/9 onto the modified surfaces was inhibited 94% and 81%, respectively. Finally, the modified PDMS showed no evidence of cytotoxic effects in in vitro assays using human skin fibroblasts.